Realizing a CO-free pathway and enhanced durability in highly dispersed Cu-doped PtBi nanoalloys towards methanol full electrooxidation. Issue 23 (3rd June 2020) - Zhao, Fengling; Ye, JinYu; Yuan, Qiang; Yang, Xiaotong; Zhou, Zhiyou
Abstract : Highly dispersed Cu-doped PtBi nanoalloys achieved by crystal phase transition are used as highly efficient and durable anode electrocatalysts for DMFCs. Abstract : Pt is the most active anode electrocatalyst for the oxidation of methanol in direct methanol fuel cells (DMFCs); however, its weak resistance to CO or CO-like species poisoning has been a matter of great concern. Therefore, the development of a highly durable anode Pt-based electrocatalyst is indispensable for large-scale application of DMFCs. Here, we demonstrate that a CO-free pathway, 6-electron full electrooxidation of methanol, is realized in highly dispersed Cu-doped PtBi alloy-phase nanocrystals by combining nuclear magnetic resonance (NMR) spectroscopy and in situ Fourier transform infrared (FTIR) spectroscopy analysis. A mass activity (MA) of 5.25 A mgPt −1 and durability for 30 hours without current decay are obtained for the PtBiCu nanoalloys. The abundant surface defects, downshift of the Pt d-band center and the dual active site of "Pt–Bi" and "Pt–Cu" endow the PtBiCu nanoalloys with faster methanol oxidation kinetics, thus enhancing activity and durability. This work provides a new strategy to synthesize alloy-phase PtBiCu nanocrystals by crystal phase transition as a highly efficient and durable anode electrocatalyst for DMFCs.